Comparative Analysis of the Influence of Empagliflozin and Dapagliflozin on the Course of Heart Failure with Associated Pathology - Nadiia M. Kulaiets (Український журнал серцево-судинної хірургії)
The aim. To compare the effectiveness of empagliflozin and dapagliflozin on the course of heart failure (HF) in patients with concomitant pathology.